Peritumoral brain edema in intracranial meningiomas Edema peritumoral em meningiomas intracranianos - Nelson de Azambuja Pereira-Filho; Fabiano Pasqualotto Soares; Ivan de Mello Chemale; Ligia Maria Barbosa Coutinho (Arquivos de Neuro-Psiquiatria)
Occurrence of peritumoral brain edema (PBE) in meningiomas has been associated with several factors in recent years, although its pathophysiological mechanism has not yet been fully elucidated. The aim of this study was to analyze the correlation between the presence / degree of PBE and factors such as gender, age, size and histological subtype of tumor. We analyzed the MRI images of 74 patients operated on Hospital Beneficência Portuguesa de Porto Alegre for the presence / degree of PBE and data was statistically correlated with the parameters of the patient. PBE was present in 70.1% of patients. Tumors with higher volume had more PBE. Tumors of the olfactory groove showed more PBE than sphenoid wing and parassagittal tumors. Transitional subtype showed more PBE than fibroblastic and meningothelial subtypes. A presença de edema cerebral peritumoral (ECP) em meningiomas tem sido associada a diversos fatores nos últimos anos, embora o seu mecanismo fisiopatológico ainda não tenha sido inteiramente elucidado. O objetivo desse estudo foi analisar a correlação entre a presença/grau de ECP e fatores como sexo, idade, volume e subtipo histológico do tumor. Foram analisadas imagens de RM de 74 pacientes operados no Hospital Beneficência Portuguesa de Porto Alegre quanto à presença/grau de ECP e os dados correlacionados estatisticamente com os parâmetros do paciente. ECP estava presente em 70,1% dos pacientes. Tumores com maior volume apresentaram mais ECP. Tumores da goteira olfatória apresentaram mais ECP que os da asa do esfenóide e que os parassagitais. Meningiomas transicionais apresentaram mais ECP que os fibroblásticos e que os meningoteliais.